„Vérnek mezeje ma az Istennek Anyaszentegyháza a mi édes nemzetünkben.” - Attila RESTÁS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
“The Lord’s Holy Church Is a Field of Blood Today in Our Beloved Nation.” Protestant Martyrdom in a Manuscript Sermon from the Teleki Archives (1675). The sermon under scrutiny is found in the archival material of the Count Teleki of Szék family (P 658), kept in the National Archives of Hungary. It is not unknown to research, although it has mainly gained interest before as a source for the history of books and libraries. The 13 manuscript pages contain the date 1675 and the name of István Nemes, as well as reference to the Reformed College of Enyed/Aiud, but the author of the sermon is unidentified. The Biblical text used is the Song of Songs 2:2, and the topic is Protestant martyrdom. Similarly to other books of Protestant martyrdom (Foxe, Raabus, Crespin), it traces the persecution of the true Church from the Old Testament fratricide to his own time. It starts with the murder of Abel, going through the Egyptian captivity of the Jews, recalling the story of the prophets murdered by Jezebel, and the persecution of Christians under the Roman Empire, ultimately leading to the sacrifice of Christ. This list appears in a similar way with other authors of this decade of mourning too (Mihály Szőllősi, István Szőnyi Nagy); what is more, Szőllősi was Teleki’s court pastor until 1674. The sermon connects the pain felt over the trial of the pastors and teachers condemned to the galleys, the fleeing of the Reformed College of Sárospatak, the seizure of Protestant churches, and the expulsion of several pastors with the grievances of “our beloved nation”. Through this, the sermon is also a document of the political connections of the Transylvanian Reformed elite and the fugitives in Hungary, as well as the piety movements that underlie these connections.